Pembentukan Peraturan Daerah Syari’ah dalam Perspektif Hukum Tata Negara Pascareformasi - Erfina Fuadatul Khilmi (University of Jember, 2018)
Indonesia in the aftermath of Reformation, the relationship between powers of central and local governments has shifted the paradigm in which the power of central government has been transferred from centralized-authoritarian to decentralized-autonomy. One of decentralized powers of local government is by providing the power to self-regulate without certain interventions from central government, including the initiative to establish bylaws (Peraturan Daerah) as the results of local autonomy. In further development of autonomy, however, the wider decentralization and autonomy attached to local governments has been responded differently. One of such responses is the establishment of sharia bylaws in which they result in problems in the Indonesian constitutional law system. From constitutional views, bylaws in local governments other than Aceh province violate citizen’s constitutional rights by which those are not accomodated in the hierarcy of national regulations. On the other hand, however, the establishment of sharia bylaw is important as an attempt to nurture social morality. Accordingly, there should not be abandonment regarding the establishment of sharia bylaws in several local governments other than Aceh province. But, the reaffirmation is needed relating to the position of sharia bylaws in the constitutional perspective which is not only seen formally, but also materially. Keywords: Post-Reformation, Decentralization, Shari’a Bylaws, Constitutional Law